Low-temperature oxidative coupling of methane in an electric field using carbon dioxide over Ca-doped LaAlO3 perovskite oxide catalysts. (July 2017) - Yabe, Tomohiro; Kamite, Yukiko; Sugiura, Kei; Ogo, Shuhei; Sekine, Yasushi
Graphical abstract: Highlights: Methane conversion at low temperature in an electric field using carbon dioxide was investigated. La0.7 Ca0.3 AlO3-δ perovskite catalyst showed high CO2 -OCM activity than ever. Formation of La2 O2 CO3 intermediate are important for progress of the CO2 -OCM reaction. Ca incorporated in LaAlO3 perovskite played an important role for C2 hydrocarbon formation. Abstract: Methane conversion was conducted over various perovskite oxide catalysts at 423 K using carbon dioxide as an oxidant in an electric field. La0.7 Ca0.3 AlO3-δ catalyst showed high CO2 -OCM activity. The highest CO2 -OCM activity, C2 yield of 7.4%, was obtained even at 348 K, that value was higher than those of other earlier reports. Dry reforming of methane to produce syngas (H2  + CO) proceeded simultaneously, and no other byproduct was observed. Results of in-situ IR, XRD and TG measurements demonstrated that CO2 adsorption on the catalyst surface and formation of La2 O2 CO3 intermediate are important for progress of the CO2 -OCM reaction, even at low temperature in an electric field. Ca atom incorporated in LaAlO3 perovskite played an important role in C2 hydrocarbon formation.